Action research for international information technology transfer a methodology and a network model - Seror, Ann C.
The paper takes a broad approach to the subject of information technology transfer between countries and presents conclusions for national development, with strong recommendations for future research and practices.
The objective of this paper is to present a methodology for action research to support information technology transfer in a context of national development. One approach to this problem is to consider new technology implementation and organization redesign as parallel processes and to develop managerial roles for action research in an interactive network model. The action research methodology proposed here is conceived to complement technical system development with identification of requirements and constraints of organization culture and behavior. The fundamental principles of this methodology serve as a basis to formulate recommendations for future research and practice.
Keywords: Information technology transfer